Surface Engineering Of Cellulose For Heavy Metal And Pesticide Removal - Zailani, Muhammad Faizal Izuany (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
The main objective of this research is to study the feasibility of heavy metals (zinc, copper and lead) and 2,4-Dichlorophenoxy acetic acid(2,4-D) removal through adsorption using surface modified cellulose. The current methods for removal of heavy metal and pesticide from aqueous solution are uneconomical and cellulose has the potential to become an effective biosorbent. However, cellulose lack of certain properties such as what to make it effective biosorbent and therefore surface engineering through chemical modification were investigated. Oxalic acid and ethylenediamminetetraacetate (EDTA) solution were used to modify the surface of cellulose. The resultant adsorbents (oxalic acid treated cellulose and EDTA treated cellulose) were characterized by Field Emission Scanning Microscope (FESEM), Fourier Transform Infrared Spectroscopy (FTIR), and Thermogravimetric Analysis (TGA). Batch adsorption process was carried out to test the suitability of the treated celluloses for removal of the heavy metals and 2,4-D. The amount of metal ions removed depended on the contact time, initial metal ion concentration and initial pH value. The adsorption equilibrium time for copper is 90 min while for zinc and lead is 120 min. The adsorbed amount of lead was the highest among the three heavy metals. However, the adsorption capacities of both of the treated celluloses were still low compared to previous similar research using other modifying agent to remove the heavy metals. Improvisation need to be done to increase its adsorption capacity. For adsorption of 2,4-D, the results in this study showed that it was not feasible to remove the pesticide using treated celluloses as the adsorbent. Pure cellulose adsorbed the highest amount of 2,4-D at 3.9844 mg/g.